Sobre El Mundo entero como lugar extraño de Néstor García Canclini (De la Crítica, 2020)
With all the changes that society presents, it becomes essential to question how communication processes develop as well as the way in which art is perceived and affected, or what influence it can exert. Modern generations do not see literature in the same way as previous generations, as they have been exposed to very different conditions that affect their observation and reasoning skills. On the other hand, within the same generation, the social order can also be a determining factor in the way that individuals vary in their perception of what surrounds them and how the arts influence them.